Levantamiento geológico-estructural de la zona sur de la parroquia Saraguro, del cantón Saraguro provincia de Loja escala 1:50000 - González Valdez, Karla Milena (2016)
This paper " STRUCTURAL GEOLOGICAL SURVEY OF THE SARAGURO PARISH SOUTH ZONE, CANTON SARAGURO, PROVINCE OF LOJA"; has been developed taking into account the objectivity of the project to achieve a geological-structural result considering for that the topographical, geomorphological, geological, stratigraphic, lithological characteristics of the major outcrops found in the area of study, as part of the development of the detailed geological map of the Saraguro parish. To carry out this survey, it was used as a topographic base of Saraguro in a 1: 50000 scale, on which the geological mapping was performed; first it was took into account previous studies which two main ones were referenced, including one by the Military Geographical Institute (IGM), in 1973 at 1: 1000000 scale and the updated was conducted by the British Geological Survey Project in 1997 at a scale of 1: 200000 The geological survey was carried out by a tour in the study area, identifying and describing the main outcrops added to that the picking of samples that will serve for microscopic and macroscopic analysis. The Saraguro parish covers an area of 17,414.11 ha; while the polygon of the study area is 3160.46 ha, taking as reference the topographic base of Saraguro, considering that the remaining part of the south zone is already mapped on the topographic map "Las Juntas". The interpretation of the obtained information as lineations, contacts, folds, faults, jointing and lithology, have been determined through a systematic process of four phases, which have allowed us to upgrade to detail geological structures. The study area is made of volcanic and plutonic igneous rocks showing the presence of massive bodies of dacitic tuffs and rhyolitic with presence of quartz and biotite as major minerals, while in the panamerican highway that serves as a connection with Oña, it was identified andesite of fine-grained dark color and abundance of plagioclase; and a sector characterized by sedimentary material as microconglomerate, produced by different tectonic processes. In the southeast sector of the area, the presence of granitoids is evident from what it can be referred that near the sector it emerges part of the Pichinal Pluto, and the presence of andesitic dykes aplitic with diameters from 0.20 to 0.50 cm. With the information we proceeded to make the geological map of the study area.